2009
DOI: 10.1007/s11101-009-9157-1
|View full text |Cite
|
Sign up to set email alerts
|

A brief resume on the genus Ailanthus: chemical and pharmacological aspects

Abstract: Over the past decade, herbal medicine has become an item of global importance, with both medicinal and economic implications. Thus, accurate scientific assessment has become a prerequisite for acceptance of herbal health claims. The plants of genus Ailanthus, belong to the family Simaroubaceae, is widely used in Ayurveda and evidence-based phytotherapy. Several species of the genus Ailanthus are widely distributed over Asia and north Australia and studied extensively over the last few decades. A compilation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 90 publications
0
35
0
Order By: Relevance
“…The composition was found to be dependent on the plant part, developmental stage, sample preparation method, and analysis. They found 9 phenolic components, although a previous study was made by Kundu and Laskar (2010) where 19 flavonoids were identified in the tissues of A. altissima. The relative content of identified compounds was found to vary between samples from different locations.…”
Section: Chemical Propertiesmentioning
confidence: 89%
“…The composition was found to be dependent on the plant part, developmental stage, sample preparation method, and analysis. They found 9 phenolic components, although a previous study was made by Kundu and Laskar (2010) where 19 flavonoids were identified in the tissues of A. altissima. The relative content of identified compounds was found to vary between samples from different locations.…”
Section: Chemical Propertiesmentioning
confidence: 89%
“…6,7 Quassinoids are reported for their various biological activities such as antitumor, anti-malarial and anti-inflammatory effects. 8 As a part of our ongoing project to search novel, plant-derived anti-inflammatory agents, a 70% EtOH extract of the stem barks of A. altissima was shown to exhibit significant inhibitory activity in a preliminary in vitro screening on LPS-induced nitric oxide, a pro-inflammatory mediator, in RAW 264.7 cells (IC 50 value of 23.84 µg/mL). Repeated chromatography of the EtOAc-and BuOH-soluble fractions from the stem barks of A. altissima led to the isolation of three new canthinone type alkaloids (1-3), along with twelve known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…8 As a part of our ongoing project to search novel, plant-derived anti-inflammatory agents, a 70% EtOH extract of the stem barks of A. altissima was shown to exhibit significant inhibitory activity in a preliminary in vitro screening on LPS-induced nitric oxide, a pro-inflammatory mediator, in RAW 264.7 cells (IC 50 value of 23.84 µg/mL). Repeated chromatography of the EtOAc-and BuOH-soluble fractions from the stem barks of A. altissima led to the isolation of three new canthinone type alkaloids (1-3), along with twelve known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). 9 The structures of known compounds were identified to be shinjudilactone (4), 5 ailanthone (5), 5 shinjulactone A (6), 5 shinjuglycoside B (7), 10 4-hydroxybenzoic acid (8), 11 vanillic acid (9), 12 3-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-propan-1-one (10), 13 p-coumaric acid (11), 14 ferulic acid (12), 11 trans-4-O-β-D-glucopyranosyl ferulic acid (13), 15 isofraxidin (14), 16 Table 2).…”
mentioning
confidence: 99%
“…In the present study, ailanthone was successfully isolated from A. altissima. Ailanthone has a wide spectrum of biological activities, including anti-allergic, anti-malarial, anti-HIV, anti-inflammatory, anti-ulcer and anti-microbial activities (18,19). Ailanthone has been demonstrated to exhibit in vitro growth-inhibitory effects against several cancer cell lines, including HepG2, Hep3B, R-HepG2, HeLa and A549 cells (18,20).…”
Section: Introductionmentioning
confidence: 99%